Validation of the Prague C&M classification of Barrett’s esophagus in clinical practice - Alvarez Herrero, Lorenza; Curvers, Wouter L.; van Vilsteren, Frederike G. I.; Wolfsen, Herbert; Ragunath, Krish; Wong Kee Song, Louis-Michel; Mallant-Hent, Rosalie C.; van Oijen, Arnoud; Scholten, Pieter; Schoon, Erik J.; Schenk, Ed B. E.; Weusten, Bas L. A. M.; Bergman, Jacques G. H. M. (Endoscopy, 2013)
Background and study aims: The Prague C&M classification for Barrett’s esophagus has found widespread acceptance but has only been validated by Barrett’s experts scoring video sequences. To date, validation has been lacking for its application in routine practice during real-time endoscopy. The aim of this study was to evaluate agreement between Barrett’s experts and community hospital endoscopists when using this classification to describe Barrett’s esophagus and hiatal hernia length during real-time endoscopy.Patients and methods: Patients underwent two consecutive endoscopies performed by different endoscopists. The study was performed in two cohorts: one cohort was seen by Barrett’s experts and the other cohort by community hospital endoscopists. Landmarks were recorded according to the Prague classification. Outcomes were interobserver agreement (assessed with intraclass correlation coefficient [ICC]), absolute agreement, and relative agreement.Results: A total of 187 patients were included, with median extent of C3M5 (IQR C1 – 7 M4 – 9) for Barrett’s esophagus and 3 cm (IQR 2 – 5) for hiatal hernia length. ICC was 0.91 (95 % confidence interval [CI] 0.88 – 0.93) for maximum length, 0.92 (95 %CI 0.90 – 0.94) for circumferential extent, and 0.59 (95 %CI 0.49 – 0.68) for hiatal hernia length. Absolute agreement within ≤ 1 cm was 74 % (95 %CI 68 – 80) for circumference, 68 % (95 %CI 62 – 75) for length, and 63 % (95 %CI 56 – 70) for hiatal hernia length. Relative agreement was 91 % for Barrett’s esophagus and 80 % for hiatal hernia length. Barrett’s experts and community hospital endoscopists showed no differences in agreement. Shorter Barrett’s segments (≤ 5 cm) had lower agreement compared with longer segments (> 5 cm).Conclusions: Agreement was good for Barrett’s esophagus and reasonable for hiatal hernia length. These findings strengthen the value of the Prague C&M classification to describe Barrett’s esophagus and hiatal hernia length. Although absolute agreement during real-time endoscopy was high, one should anticipate that Barrett’s values may vary by 1 – 2 cm between two endoscopies.